Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Terhadap Produktivitas Kerja Karyawan Pada Selyca Mulia Hotel Samarinda - Winda Siwi Harnum (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to determine the effect of occupational safety and health on employee work productivity at the Selyca Mulia Hotel Samarinda. The population in this study as well as the sample were employees at the Selyca Mulia Hotel Samarinda, totaling 61 people. This research is quantitative research with descriptive analysis. The data collection method is using questionnaires, interviews, observation and documentation. Data analysis uses multiple linear regression techniques using SPSS version 23. The results of the research show that Occupational Safety (X1) and Occupational Health (X2) together (simultaneously) influence employee work productivity (Y). Work Safety (X1) partially has a positive and significant effect on employee work productivity (Y) at the Selyca Mulia Hotel Samarinda. Occupational health (X2) partially has a positive and significant effect on employee work productivity (Y) at the Selyca Mulia Hotel Samarinda. The results of the regression test show that the correlation coefficient value for the work safety variable is 0.231 or 23.1%, which is positive, meaning that work safety is in the same direction or directly proportional to work productivity and the partial test results show that the t-count value for the work safety variable is t table value with an error level of α ( 0.05) of 5.853 > 2.002 or tcount > ttable. The results of the regression test show that the correlation coefficient value for the occupational health variable is 0.148 or 14.8%, which is positive, meaning that occupational health is in the same direction or directly proportional to work productivity and the results of the partial test show that the t value of the occupational health variable is equal to ttable value with an error level of α ( 0.05) of 3.363 > 2.002 or tcount > ttable.